Optimizing Supply Delivery Times to Reduce Lost Sales and Logistics Costs in a Technical Services Company - Alfaro Rosas, Jorge Luis; Vargas Benitez, Elvira Marleni; Vilchez Alvarez, Cielo Guadalupe; Zambrano Martos, Allison Dayana (LACCEI, 2025)
The main objective of this project is to propose a logistics optimization model to improve supply delivery times in a Technical Services Company. The study addresses a critical issue related to delays in technical service response and product delivery, resulting in losses equivalent to 13% of the company’s annual revenue. This is an applied, mixed-method, and descriptive research that employs tools such as surveys, process analysis, mathematical modeling using LINGO, and the Odoo ERP system. The project has an operational and geographic scope focused on the city of Trujillo, encompassing internal processes related to logistics, inventory, and customer service. The implementation is expected to reduce delays by 30%, generate annual savings of S/ 9,000, and improve operational efficiency by 15%. The impact will directly benefit operational staff, institutional clients, and the company’s overall profitability